2020
DOI: 10.1200/jco.2020.38.15_suppl.10002
|View full text |Cite
|
Sign up to set email alerts
|

First safety and efficacy results of PRADO: A phase II study of personalized response-driven surgery and adjuvant therapy after neoadjuvant ipilimumab (IPI) and nivolumab (NIVO) in resectable stage III melanoma.

Abstract: 10002 Background: OpACIN-neo tested 3 dosing schemes of neoadjuvant (neoadj) IPI+NIVO and identified 2 cycles of IPI 1mg/kg + NIVO 3mg/kg (I1N3) as the most favorable with a pathologic (path) response rate (pRR) of 77% and 20% grade 3-4 irAEs. After 17.6 months median FU, 1/64 (2%) patients (pts) with path response vs 13/21 (62%) of the non-responders ( > 50% viable tumor cells; pNR) had relapsed. We hypothesized that therapeutic lymph node dissection (TLND) could be omitted in pts achieving a complete or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 0 publications
0
59
0
2
Order By: Relevance
“…An experimental extension cohort (PRADO; n = 99) of this trial reported that therapeutic lymph node dissection was omitted in 97% of the patients who achieved a complete or near-complete pathological response (≤10% viable tumor cells), therefore reducing surgical morbidity [ 32 ]. The previously reported high-grade toxicity of this trial varied between arms: grade 3–4 adverse events were seen in 40% of patients in arm A, 20% in arm B, and 50% in arm C. The most common grade 3–4 adverse events were elevated liver enzymes in group A (20%) and colitis in group C (19%); in group B, none of the grade 3–4 adverse events were seen in more than one patient.…”
Section: Neoadjuvant Settingmentioning
confidence: 99%
“…An experimental extension cohort (PRADO; n = 99) of this trial reported that therapeutic lymph node dissection was omitted in 97% of the patients who achieved a complete or near-complete pathological response (≤10% viable tumor cells), therefore reducing surgical morbidity [ 32 ]. The previously reported high-grade toxicity of this trial varied between arms: grade 3–4 adverse events were seen in 40% of patients in arm A, 20% in arm B, and 50% in arm C. The most common grade 3–4 adverse events were elevated liver enzymes in group A (20%) and colitis in group C (19%); in group B, none of the grade 3–4 adverse events were seen in more than one patient.…”
Section: Neoadjuvant Settingmentioning
confidence: 99%
“…As a result of this definition, non-TDLN may sometimes be more proximal to the tumor than TDLN, but due to the fact that tumor-derived factors will diffuse through the lymph basin, be less affected by the tumor, e.g., in terms of immune suppression (9). A growing number of studies are exploring the use of systemically administered immune checkpoint inhibitors (ICI) as neo-adjuvant therapy for patients in earlier (i.e., resectable) cancer stages (10)(11)(12)(13). As in this setting both the primary tumor and TDLN are still in place (rather than surgically removed in the adjuvant setting) this approach will enable simultaneous immune modulation of the TME and of TDLN.…”
Section: Introductionmentioning
confidence: 99%
“…The first results show again a high pathologic response rate of 71%, and patients with MPR in whom extensive surgery was omitted had reduced surgical morbidity and higher quality of life scores. 18 The RFS data are still immature with a median follow-up of less than a year.…”
Section: Neoadjuvant Checkpoint Inhibition - New Aspects In An Old Comentioning
confidence: 99%